Depressive symptoms in acromegaly: factors that affect their incidence and severity? - Malicki, Adam; Malicka, Joanna; Potembska, Emilia; Zwolak, Agnieszka; Malicki, Dariusz; Rogowska, Patrycja (Journal of Medical Science, 2020)
Aim. The study aimed to evaluate the influence of acromegaly on the prevalence and the severity of depressive symptoms in patients with active and inactive disease. Material and Methods. The study group comprised 56 patients with acromegaly, which were divided into two groups based on growth hormone (GH) and insulin-like growth factor (IGF-1) levels, with controlled/cured and with uncontrolled acromegaly. The presence and severity of depressive symptoms were assessed using the Beck Depression Inventory-II (BDI-II). Results. The mean score of BDI-II in the whole group of patients was 13.43±10.41, with no significant difference in the severity of depressive symptoms between patients with cured/controlled and uncontrolled acromegaly (p=0.620). Similarly, the lack of statistically significant differences was confirmed in patients with micro- and macroadenomas, as well as with and without hypopituitarism. There were no significant correlations between BDI-II scores and GH or IGF-1 levels, patient age or duration of the illness. Conclusions. Depressive symptoms are common in acromegalic patients even if remission has been attained. They are most likely caused by psychological, non-organic causes. Patients diagnosed with acromegaly should undergo a screening BDI test as a part of comprehensive care, and in the event of elevated levels should be provided with a psychiatric consultation and psychological care.